The relationship between individual-level socioeconomic status and preference for medical service in primary health institutions: a cross-sectional study in Jiangsu, China - Miao, Chunxia; Fang, Xin; Sun, Hong; Yin, Yani; Li, Bo; Shen, Wenxing; Chen, Jie; Huang, Xiaojing (Frontiers in Public Health, 2024)
Background: While China's primary health care (PHC) system covers all citizens, the use of medical services supplied by primary health institutions (PHIs) is not at ideal levels. This study explored the impact of socioeconomic status (SES) on residents' first choice of medical services provided by PHIs.Methods: This community-based, cross-sectional study was conducted in Jiangsu Province, China, from October 2021 to March 2022. A custom-designed questionnaire was used to evaluate 4257 adults, of whom 1417 chose to visit a doctor when they were sick. Logistic regression was used to test the relationships among SES, other variables and the choice of medical services, and interaction effects were explored.Results: A total of 1417 subjects were included in this study (48.7% female; mean age 44.41±17.1 years). The results showed that older age (p<0.01), rural residence (p<0.01), a preference for part-time medical experts in PHIs (p<0.01), and lack of coverage by basic medical insurance (p<0.05) were associated with the first choice to use PHIs. In the multiple logistic regression model, SES was not associated with the first choice of medical services supplied by PHIs (p>0.05), but it interacted with three variables from the Commission on Social Determinants of Health Framework (material circumstances, behaviours and biological factors, and psychosocial factors).Vulnerable individuals who are the target visitors to PHIs are older, live in rural areas, and suffer from chronic diseases. SES, as a single factor, did not impact whether medical services at PHIs were preferred, but it mediated relationships with other factors.